2012
DOI: 10.21608/jpp.2012.84974
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NPK Rates and Humic Acid Applications on Growth of Egyptian Cotton

Abstract: Two field experiments were carried out at Gemmeiza Agric. Res. Station, El-Gharbia Governorate during 2010 and 2011 seasons, to study the effect of four NPK fertilizers rates (100 %, 75 %, 50 % and 25 % of recommended rate) and application methods of humic acid on growth of the Egyptian cotton cultivar "Giza 86". The recommended rate of NPK was 45 kg N +22.50 kg P2O5 + 24.0 kg K2O/ fed.. The solutions of humic acid were applied with the concentration of 5 cm 3 /litre as a soaking seed for 18 h, 50 cm 3 /litre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 1 publication
4
5
0
Order By: Relevance
“…The boll weight and seed index increases due to the high NPK level was mainly attributed to increase photosynthetic activity of cotton plants and consequently increase accumulation of metabolites with direct impact on boll weight and seed index. These results are in accordance with those outlined by overall plant growth, fruit retention, seed cotton yield and its components, Seadh et al, (2012), Emara et al, (2015 and2016), Elhamamsey et al, (2016) and Emara and Abdel-Aal (2017c). The micronutrients treatments had a significant effect on number of open bolls/plant and boll weight in 2016 and 2017 seasons and seed cotton yield/feddan in 2017 season only, but the insignificant effect on, seed index and lint percentage in both seasons.…”
Section: C-yield and Yield Componentssupporting
confidence: 91%
See 1 more Smart Citation
“…The boll weight and seed index increases due to the high NPK level was mainly attributed to increase photosynthetic activity of cotton plants and consequently increase accumulation of metabolites with direct impact on boll weight and seed index. These results are in accordance with those outlined by overall plant growth, fruit retention, seed cotton yield and its components, Seadh et al, (2012), Emara et al, (2015 and2016), Elhamamsey et al, (2016) and Emara and Abdel-Aal (2017c). The micronutrients treatments had a significant effect on number of open bolls/plant and boll weight in 2016 and 2017 seasons and seed cotton yield/feddan in 2017 season only, but the insignificant effect on, seed index and lint percentage in both seasons.…”
Section: C-yield and Yield Componentssupporting
confidence: 91%
“…In this respect Seadh et al, (2012) and Hamoda et al, (2014) found that the final plant height, no. of fruiting branches/plant, number of bolls/plant, boll weight, seed index, lint percentage and seed cotton yield/plant and /fad.…”
Section: Introductionmentioning
confidence: 86%
“…Table 1. Maximum plant height (67.6 cm) was observed applying T3 [7], the performance of plant growth parameters changed with humic acid and the NPK application rate and the plants had better growth under maximum concentration. Nutrient uptake, especially of nitrogen, phosphorous and sulfur is improved by the activity of humic acid [8].…”
Section: Treatmentmentioning
confidence: 96%
“…Foliar spray of humic acid at the rate of 0Á1% showed a significant increase in uptake of nutrients than the control (Tenshia and Singaram 1992). Increased plant growth by application of humic acid was observed in Gerbera jamesonii L. (Nikbakht et al 2008), cotton (Seadh et al 2012), wheat (Mackowiak et al 2001), cucumber (Rau- than and Schnitzer 1981) and marigold, pepper and strawberry plants (Arancon et al 2006).…”
Section: Discussionmentioning
confidence: 98%
“…), cotton (Seadh et al . ), wheat (Mackowiak et al . ), cucumber (Rauthan and Schnitzer ) and marigold, pepper and strawberry plants (Arancon et al .…”
Section: Discussionmentioning
confidence: 99%